Vademecum of specialties / Laboratorio Hispanoamericano. (LHISA, 2002)
Anti-inflamatories.--Antiparasitics.--Poultry.--Nutrition and didinfection.--reproduction and mammary glands.--Veterinary spacialties.--Oral.